Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt Xyz - Fajri Anggita Putri; Kristiana Sri Utami (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
PT XYZ is a company operating in the food and beverage sector, with an Asian specialty menu of yamie. The purpose of this study is to determine how work discipline and compensation impact employee performance at PT XYZ, because the good and bad of an employee will affect the performance of his company. The method applied is a quantitative method. The results of the t test analysis show that the compensation variable () has no significant effect on the employee performance variable (Y) of PT XYZ, this is indicated by the sig value. the number is greater than 0.05, namely 0.368 > 0.05. And the work discipline variable () has a positive and significant effect on the employee performance variable (Y) of PT XYZ, which is indicated by the value of this figure less than 0.05, namely 0.011 <0.05. In the F test results, compensation and work discipline simultaneously have a positive and significant effect on employee performance with a significant value of 0.008.